Replacement of degraded articular cartilage using stem cell-based therapy in rabbit model of osteoarthritis - M. Abofila, Marwan Taher (2012)
Osteoarthritis (OA) is a degenerative disease of the joint characterized by the degradation of articular cartilage, with loss of matrix, and cyst and osteophyte formation. Osteoarthritis is the most common form of arthritis, and mostly results in physical disability. Treatments of osteoarthritis with stem cells appear to be a practical and effective, resulting in enhanced repair of damaged tissues. In vivo systems, the ability of autologous mesenchymal stem cells, in both humans and animals, to regenerate lost articular cartilage in OA has clearly been proven. The general aim of this study was to evaluate the effectiveness of rabbit bone marrow-derived stem cell (allogeneic stem cells) and human umbilical cord-derived stem cell (xenogeneic stem cell) therapies in comparison with sodium hyaluronate, as potential replacements for degraded articular cartilage in monosodium iodoacetate-induced osteoarthritic rabbit models. Assessment parameters included clinical signs, radiographic and histopathological evaluation of affected joints, gross assessment of muscle and joints, and cytokine levels (IL-1, IL-4, IL-10 and TNFα) in plasma and serum. Thirty male New Zealand white rabbits were used in this study. OA was induced by a single intra-articular injection of 2.5 mg of monosodium iodoacetate (MIA) / 0.3 ml normal saline (NS). Five milliliters of bone marrow were aspirated from the rabbit‘s iliac crest and cultured in vitro. The rabbits were divided into five groups (n=6); 1. Human stem cell-treated group (HSTG), 2. Rabbit stem cell-treated group (RSTG), 3. Sodium hyaluronate-treated group (SHTG), 4. Media stem cell-treated group (MSTG), and 5. Normal saline-treated group (NSTG). The results showed that there were significant differences (P < 0.05) in body weights, voluntary movement and size of joints among all groups at week 20 post OA induction (16 weeks post injection treatments). In terms of clinical outcomes, treatment with rabbit bone marrow-derived stem cells (allogeneic stem cells) and human umbilical cord-derived stem cells (xenogeneic stem cells) produced better outcomes, and treatment with sodium hyaluronate was not as effective. Treatments with the media and normal saline were the least effective in this regard. There was significant suppression of catabolic cytokines in the RSTG (P < 0.05) compared to other groups, which showed no significant differences (P > 0.05), at 12, 16 and 20 weeks. Furthermore, there were significant differences (P < 0.05) among all groups in the radiological scoring of affected stifle joints of rabbits at week 20. Results of radiographical scoring for the treated stifle joint were best in the RSTG and HSTG, which showed healing and a reversal to normal appearance. That of the SHTG revealed slow OA progression, while MSTG and NSTG scored the worst. There were significant differences (P < 0.05) among all groups in the grading of gross lesions in the OA stifle joints of rabbits at week 20. The degree of OA grading was best for the RSTG, which revealed normal (no change) to mild changes in stifle joint structures while the HSTG showed mild to moderate changes in the joint structures. The SHTG on the other hand showed moderate changes and the MSTG and NSTG had the most severe gross lesions as demonstrated by severe to very severe pathological changes in joint structures. The differences in sizes and masses of the quadriceps femoris muscles between treated and untreated contra-lateral joints were significantly different (P < 0.05) among all groups at week 20. Disuse atrophy of the affected joints was obvious in the MSTG and NSTG, while only slight atrophy was noted in SHTG, and no atrophy was noted in both the RSTG and HSTG. Histopathological scoring on the stifle joints at week 20 showed significant differences (P < 0.05) between all the groups. The RSTG showed the best histopathological scoring, followed by the HSTG and SHTG, while the MSTG and NSTG showed the worst scores. In conclusion, single intra-articular injection of rabbit bone marrow-derived stem cells (allogeneic stem cells) or human umbilical cord-derived stem cells (xenogeneic stem cells) could promote the regeneration of damaged articular cartilage in OA as evidenced by improved radiological and pathological outcomes, with resultant improvements in general mobility, and relief of symptoms and pain.